2016
DOI: 10.1039/c6ce00681g
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, crystal structures and luminescence properties of lanthanide-based coordination polymers constructed from a functionalized terpyridyl carboxylate ligand

Abstract: Six families of new lanthanide coordination polymers, [Ln 2 (L) 6 (H 2 O) 2 ] n •3nH 2 O (Ln = Nd (1), Sm (2), Eu (3), Gd (4), Tb (5), Dy (6), Ho (7), Er (8), Yb ( 9 14), Gd (15), Er ( 16)), (HL = 4′-(2-carboxyphenyl)-4,2′:6′,4″-terpyridine, H 2 ox = oxalic acid, H 2 glu = glutaric acid, H 2 adip = adipic acid, H 2 (1,2-bdc) = benzene-1,2-dicarboxylic acid) were synthesized under hydrothermal conditions and characterized by elemental analysis, IR and single crystal X-ray diffraction. Compounds 1-9 are isomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…According to previous work, compared with single carboxylate‐coordinated Eu/Tb complexes, mixed oxalate‐assisted coordinates have paid much attention due to their polydentate, easy to synthesize and noticeable synergy effects on fluorescence properties. Li and Hu et al, , reported that mixed Eu/Tb frameworks display highly efficient red/green emissions based on the mixed ligand. But the application of mixed Eu/Tb single‐oxalate complexes for the fluorescence modulation has merely not investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous work, compared with single carboxylate‐coordinated Eu/Tb complexes, mixed oxalate‐assisted coordinates have paid much attention due to their polydentate, easy to synthesize and noticeable synergy effects on fluorescence properties. Li and Hu et al, , reported that mixed Eu/Tb frameworks display highly efficient red/green emissions based on the mixed ligand. But the application of mixed Eu/Tb single‐oxalate complexes for the fluorescence modulation has merely not investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The mixed Ln ‐MOFs materials, especially Eu/Tb mixed MOFs, play an important role in the preparation of luminescent materials with application in display devices, greatly improving the deficiency of the traditional physical mixing methods in fabrication process, stability, and reproduction . In general, multiple color emission can be accomplished by adjusting the proportion of different color via controlling the Ln III ions ratio and the excitation wavelength of mutually doped Ln ‐MOFs . For example, Hu et al reported two Eu/Tb doped compounds exhibiting tunable white‐light emission, whose luminescent colors can be turned easily …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The architectures of the numerous carboxylate-based MOFs are well defined with reticular chemistry, partly due to their prominent metalcarboxylate secondary building units (SBUs) (Furukawa et al, 2013;Du et al, 2014). Carboxylic acids as bridging ligands usually have two advantages: first, carboxylic acids have rich coordination modes with metal ions; secondly, depending on the degree of deprotonation, the carboxyl group itself can act as a hydrogen-bond acceptor and donor (Deacon & Phillips, 1980;Xu et al, 2016;. Based on these considerations, recently, a few novel 3D MOFs with a rare lsz topology (Zhang et al, 2018), a unique binodal 3,20-connected network (Zhao et al, 2016), an unprecedented 3D/3D heterointerpenetrating framework composed of a dia and a bcu topology (Xu et al, 2012;Luo et al, 2014), and an unusual infinite nano-sized ribbon (Zhang et al, 2011) have been successfully assembled from the symmetrically substituted biphenyldicarboxylic acids (H 2 BPDC).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the selection of appropriate organic ligands, which function as chromophores that transfer absorbed energy efficiently to the excited states of Ln 3+ ions, is significant for Ln 3+ compounds to optimize their luminescence and enhance their emission efficiency (Moore et al, 2009;Zheng et al, 2007;Mahapatra et al, 2018;Zheng et al, 2014). Terpyridine-based derivatives are admirable chromophoric antenna ligands, and they are widely used as effective building blocks for lanthanide coordination compounds (Zheng et al, 2014;Smith et al, 2012;Wu et al, 2011b;Xu et al, 2016;Liu et al, 2012;Bretonniè re et al, 2002).…”
Section: Introductionmentioning
confidence: 99%